Designing job ads to stimulate the decision to apply: a discrete choice experiment with business students. Issue 15 (22nd August 2022) - Petry, Tanja; Treisch, Corinna; Peters, Mike
Abstract: This study advances a differentiated understanding of job ad pre-hire effectiveness. It analyzes the utility values for varying levels of job ad attributes through a hierarchical Bayesian approach to conjoint analysis. This method allows not only to measure the relative importance of different attributes on the individual level but also to explore heterogeneity in evaluations influenced by educational level, international career orientation and time to graduation. The main results from the experiment show that for both undergraduate and graduate business students, salary and opportunity for advancement by far outweigh employer familiarity and the description of job-related tasks. The study contributes to the recruitment literature by assessing to what extent these four core attributes of a job ad drive job pursuit intentions. It also discusses the implications of attribute trade-offs for employer branding activities.